PENGEMBANGAN E-BOOK BERGAMBAR UNTUK MENCEGAH PERILAKU BULLYING DI KELAS IV SD NEGERI 1 TALANG PADANG - sulistiawati; Endie Riyoko; Endang Surtiyoni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
ABSTRACT This study aims to develop an illustrated e-book media to prevent bullying behavior in the fourth grade of SD Negeri 1 Talang Padang. The research method used is Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research subjects were fourth-grade students of SD Negeri 1 Talang Padang. Data collection techniques included observation, interviews, questionnaires, and documentation. The data analysis techniques used were validity analysis and practicality analysis. The results of material expert validation showed a validity level of 92.5%, media expert validation was 90%, and language expert validation was 87.5%. The practicality of the e-book tested on 30 students was 82%. These results indicate that the illustrated e-book media is very valid and practical in improving students' knowledge and attitudes in preventing bullying. Therefore, this illustrated e-book can be an alternative solution in efforts to create a safe and comfortable school environment for student